Twórczość Tadeusza Różewicza w radiu - Zwolińska, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
In the article I focus on the works of Tadeusz Różewicz presented on Polish Radio, of which the most numerous are the works of dramatic art adapted for radio, such as: Akt przerywany [The Interrupted Act], Białe małżeństwo [White Wedding], Kartoteka [The Card Index], Kartoteka rozrzucona [The Card Index Scattered], Odejście Głodomora [The Starveling Leaves], Pogrzeb po polsku [Polish funeral], Stara kobieta wysiaduje [The Old Lady Sits Waiting], Śmieszny staruszek [The Funny Old Man], Świadkowie albo nasza mała stabilizacja [The Witnesses, or our little stabilisation], Wyszedł z domu [He Left Home]. Apart from this, Różewicz’s one acters have been broadcast as radio dramas titled Teatr niekonsekwencji [Theatre of Inconsistency]. His poetry have been utilised with varying degrees of success, forming the basis for such poetic programmes as Radio w radiu [Radio on radio], based on a selection of poems from the volumes Uśmiechy [Smiles], or Recykling [Recycling]. A separate group is constituted by programmes forming a kind of tribute to poetic masters: Prus (Rozmowy w Alei Zdrowia) or Staff (Tadeusz Różewicz pisze Staffa). Apart from this, I’m interested in programmes presenting the author’s prose in the collected work Matka odchodzi [Mother Leaves], and also the cycle of five interviews Dialogi poetów. Rozmowy o życiu [Poets’ Dialogue. Conversations about life], being the result of the meeting of Tadeusz Różewicz and Czesław Miłosz in the Teatr Słowacki in Kraków in July 1999. Comparing the radio versions of the texts of these dramas, I arrive at the conclusion that in the majority of cases the directors and engineers of these adapted dramas, falling back on the caveat “based on”, made bold choices, shortening individual scenes or omitting them entirely. In addition, I consider that the creators of these dramas were not attempting to excessively modernise Różewicz’s art, maintaining their climate, their specific rhythm, based on their fragmentary nature, the sequence of scenes as well as the poetics of collage and recycling.